Pengaruh Pendidikan Kesehatan dan Konseling Terhadap Kualitas Hidup Wanita Menopause - Eltanina Ulfameytalia Dewi; Yohana Entan Perwati (Elisabeth Health Jurnal, 2021)
Introduction : Knowledge is the result of knowing, and this happens after people sensing a certain object. caring behavior is a basic form of nursing practice with patience, honesty, confidence, presence, touch, affection. In general Caring behavior is an action that is based on care, compassion, skills, empathy, responsibility, and support. The purpose of this research is to find out the description of the knowledge of third-level nurses about caring behaviour at STIKes Santa Elisabeth Medan in 2020. Method : This study uses a qualitative method where the data collection is done by interviewing as many as 5 questions so as to be able to dig deeper about behaviour caring knowledge. The sampling technique uses simple random sampling of 5 participants. The data analysis technique used is thematic analysis. The results obtained: Result : Caring is a form of caring, caring, actions towards others and others. Caring behavior is a behavior or habit of caring for others and others. Caring behavior is a way for someone to meet the needs of patients during treatment, both physical needs and emotional needs of patients. Conclusion : How to provide caring behavior in nursing practice by giving attention, affection, security and comfort both with touch, presence and action. Concerns when giving caring behavior in nursing practice in approaching patients, when speaking often feel less confident. The problems faced in nursing practice are ego, emotional attitude and lack of respeck from the patient which makes attitudes and actions more uncaring and less confident in taking action.